Learning Strategies And Styles of UMSU Medical Faculty Students During the COVID-19 Pandemic - Nurfansyah, Gading; Utami, Ratih Yulistika (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: The COVID-19 pandemic significantly altered medical education, prompting a shift from face-to-face to online and blended learning at the Faculty of Medicine Universitas Muhammadiyah Sumatera Utara (FK UMSU). This study analyzed dominant learning styles and strategies among 206 medical students from the 2020 (fully online) and 2021 (blended learning) cohorts during the pandemic. Using the VARK questionnaire and Revised Two-Factor Study Process Questionnaire (R-SPQ-2F), findings revealed visual learning as the most prevalent style (34%), particularly in the blended learning cohort. Auditory preferences were more common among fully online learners, while read/write and kinesthetic styles were less dominant. Regarding strategies, 57% of students adopted surface learning approaches, focusing on rote memorization, whereas 43% employed deep strategies emphasizing conceptual understanding. Surface learning was notably higher in the 2021 cohort exposed to blended formats, suggesting a potential disconnect between hybrid environments and meaningful engagement. The study highlights how instructional delivery modes influenced learning behaviors: blended learning fostered visual dominance and marginally supported deeper strategies, while fully online formats correlated with auditory preferences and surface-level tactics. These insights underscore the need for adaptive pedagogical approaches in post-pandemic medical education, tailored to diverse learning preferences and strategies to enhance academic outcomes. Institutions should consider integrating multimodal resources and fostering interactive environments to bridge gaps between online, blended, and traditional learning systems.